Associations of short sleep duration with appetite‐regulating hormones and adipokines: A systematic review and meta‐analysis. (15th June 2020) - Lin, Jianfei; Jiang, Yanrui; Wang, Guanghai; Meng, Min; Zhu, Qi; Mei, Hao; Liu, Shijian; Jiang, Fan
Summary: In the current study, a systematic review and meta‐analysis were conducted to summarize and assess whether short sleep duration is associated with appetite‐regulating hormones and adipokine levels. Reference databases were searched for studies related to sleep and appetite‐regulating hormones and adipokines. Qualitative and quantitative syntheses were conducted to evaluate the relationship between sleep duration and the level of appetite‐regulating hormones and adipokines, including leptin, ghrelin, adiponectin, resistin, and orexin. Twenty‐one of 3536 studies, covering a total of 2250 participants, met the inclusion criteria. Leptin, ghrelin, and adiponectin were included in the meta‐analysis. Ghrelin levels were higher in the short sleep group (standard mean difference [SMD] = 0.14, 95% CI [0.03, 0.25], p = 0.01). Significant differences between the short sleep group and recommended sleep group were also noted in leptin level experimental subgroup studies (SMD = 0.19, 95% CI [0.03, 0.35], p = 0.02) and ghrelin level cross‐sectional subgroup studies (SMD = 0.14, 95% CI [0.02, 0.27], p = 0.03). A rise in leptin and ghrelin levels were also observed in sleep deprivation groups (SMD = 0.24, 95% CI [0.10, 0.39], p = 0.001 and SMD = 0.18, 95% CI [0.04, 0.33], p = 0.01, respectively). In conclusion, short sleep duration is associated with an increased ghrelin level, while sleep deprivation had a significant effect on the levels of both leptin and ghrelin.